Optical Principles of Fluorescence-Guided Brain Tumor Surgery: A Practical Primer for the Neurosurgeon. Issue 3 (30th July 2018) - Zhang, Daniel Y; Singhal, Sunil; Lee, John Y K
Abstract: Fluorescence-guided surgery is a rapidly growing field that has produced some of the most important innovations in surgical oncology in the past decade. These intraoperative imaging technologies provide information distinguishing tumor tissue from normal tissue in real time as the surgery proceeds and without disruption of the workflow. Many of these fluorescent tracers target unique molecular or cellular features of tumors, which offers the opportunity for identifying pathology with high precision to help surgeons achieve their primary objective of a maximal safe resection. As novel fluorophores and fluorescent probes emerge from preclinical development, a practical understanding of the principles of fluorescence remains critical for evaluating the clinical utility of these agents and identifying opportunities for further innovation. In this review, we provide an "in-text glossary" of the fundamental principles of fluorescence with examples of direct applications to fluorescence-guided brain surgery. We offer a detailed discussion of the various advantages and limitations of the most commonly used intraoperative imaging agents, including 5-aminolevulinic acid, indocyanine green, and fluorescein, with a particular focus on the photophysical properties of these specific agents as they provide a framework through which to understand the new agents that are entering clinical trials. To this end, we conclude with a survey of the fluorescent properties of novel agents that are currently undergoing or will soon enter clinical trials for the intraoperative imaging of brain tumors.